Resistência antimicrobiana de enterobactérias de aves migratórias no litoral paraibano - Silva, Cristiane Ribeiro da (2018)
Migration is a biological behavior of several bird species and may favor the spread of pathogenic microorganisms over long distances, putting populations of other species of birds, mammals, including humans at risk. Many of these microorganisms may be resistant to some types of antibiotics and pose a threat to public health. The objective of this study was to isolate, characterize and evaluate the resistance profile of enterobacteria found in species of tortoises in the wintering season in Paraíba. Cloacal samples of the species Arenaria interpres, Calidris pusilla, Charadrius semipalmatus and Tringa flavipes were collected. Seventeen strains were isolated from 14 different bacterial genera for which 12 antibiotics were tested; (68.8%) was observed for all genuses against amoxicillin + clavulanic acid, followed by cefoxitin (63.8%) and ampicillin (63,8%); Of the bacterial strains that presented phantom halo, 6 (12.76%) strains were resistant to aztreonam, 1 (2.12%) were resistant to ceftazidime, 1 (2.12%) to cefoxitin, and 1 (2.12% ) resistant to Cefotaxime. Therefore, it is important to monitor wild birds, as these are potential reservoirs of pathogenic microorganisms, thereby helping to disseminate antimicrobial resistance.